Integrating Advanced Computer Vision and AI Algorithms for Autonomous Driving Systems - Tan, Kai; Wu, Jiang; Zhou, Hong; Wang, Yixu; Chen, Jianfeng (Journal of Theory and Practice of Engineering Science, 2024)
Autonomous vehicle is a typical high-tech comprehensive application, including scene perception, optimization calculation, multi-level assisted driving and other functions, using computer vision, sensors, information fusion, information communication, high-performance computing, artificial intelligence and automatic control and other technologies. In these technologies, computer vision, as a direct entry point to data processing, is an integral part of autonomous driving. Secondly, it brings revolutionary changes to the future transportation system. The application of image processing and computer vision in autonomous driving plays a key role in enabling vehicles to perceive and understand the surrounding environment and achieve intelligent decision-making and control. Therefore, in combination with the application of computer vision and artificial intelligence in automatic driving, this paper expounds the image processing technology in automatic driving, including camera and sensor technology, image acquisition and preprocessing, feature extraction and object detection, so as to discuss the application of computer vision algorithm in automatic driving. The research on lane keeping and recognition, obstacle detection and avoidance, traffic signal and sign recognition is of great practical significance.